Enema Syringes in South Andean Hallucinogenic Paraphernalia: Evidence of Their Use in Funerary Contexts of the Atacama and Neighboring Zones (Ca. Ad 500–1500) - Echeverria-Morgado, J (Springer, 2019)
This study presents the results of our investigation of different archaeological contexts of the Atacama Desert, Northern Chile, for the purpose of identifying a specific type of bird bone tube that has been proposed as a possible enema syringe—an instrument used to introduce some kind of alkaloid into the human body through the rectal cavity as part of a psychoactive practice that was widespread in the South-Central Andes during pre-Hispanic times. To address methodological requirements—such as the need to identify new specimens from known contexts within museum collections in Chile and abroad and the need for chemical-organic analyses to identify the function of these tubes—we gathered a sample of tubes from funerary contexts in different parts of the Circumpuna area. The 25 identified specimens were characterized morphologically and technically, and the residues found were subjected to organic-chemical analysis. We present the evidence derived from one of these tubes, on the basis of which we conclude that this artifact is indeed an implement used to introduce alkaloids into the human body anally. Traces of coprostanol and archaeological human fecal matter were detected for the first time along with the presence of bufotenine, an alkaloid from the genus Anadenanthera, thereby confirming the connection of enemas to hallucinogenic practices. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.